Book Reviews: Theory and Applications of Spherical Microphone Array Processing; Signal Processing in Acoustics and Vibrations; The MEMS Microphone Book; and Vehicle Noise, Vibration, and Sound Quality - Fonseca, William D'Andrea; Vorländer, Michael; Mello, Felipe Ramos de; Silva, Yuri A. Ribeiro (Acústica e Vibrações, 2024)
This text brings together four book reviews that collectively provide a current and wide-ranging perspective on core topics in acoustics, vibration, and audio. The selection spans from signal-processing foundations to specialized applications in instrumentation and product engineering. “Theory and Applications of Spherical Microphone Array Processing” addresses modern concepts and tools for spherical array processing, emphasizing spatial sound-field representations as well as estimation and filtering methods. “Processamento de Sinais em Acústica e Vibrações” offers a didactic, Portuguese-language pathway that connects theory to canonical applications in the field. “The MEMS Microphone Book” approaches MEMS microphones from a practical standpoint, linking physical constraints, integration choices, and criteria for reliable, high-quality capture. Finally, “Vehicle Noise, Vibration, and Sound Quality” structures the fundamentals and practice of NVH, clarifying how measurements and models inform design trade-offs and perceived sound quality. Taken together, the reviews aim to guide readers toward deeper study while highlighting complementary viewpoints across the discipline.